Beyond gender binaries : an intersectional orientation to communication and identities - Griffin, Cindy L. (University of California Press, 2020)
"Beyond Gender Binaries uses a feminist, intersectional, and invitational approach to understanding identities and their relationships to communication. Taking readers outside the familiar binary constructions of gender and identity, Cindy L. Griffin addresses, through a feminist intersectional lens, communication, identity, power and privilege, personhood and citizenship, safety in public and private spaces, and hegemony and colonialism. Twelve chapters focus on critical learning through careful exploration of key terms and concepts, and contemporary and historical examples, as well as guides to intersectional approaches to communication. This teachable text showcases not just the ways individuals, systems, structures, and institutions use communication to privilege particular identities-discursively and materially-but also the myriad ways communication can be used to disrupt that privilege and respectfully understand the nonbinary and intersectional nature of every person's identity. Key features include: Intersectional approaches to explaining and understanding identities and communication are the foundation of each chapter and inform the presentation of information throughout the book. Contemporary and historical examples are included in every chapter highlighting the intersectional nature of identity and the role of communication in our interactions with other people. Complex and challenging ideas are presented in clear, respectful, and accessible ways throughout the book"--